A network management architecture for 6LoWPAN network - Kun Feng; Xiaohong Huang; Zhisheng Su (2011 4th IEEE International Conference on Broadband Network and Multimedia Technology, 2011)
IPv6 over low-power wireless personal area networks (6LoWPAN), composed by large number of constrained devices with wireless communication ability, are becoming more and more important, not only because their reduced cost but also a lot of real world applications and their ability to connect to IP networks. Since devices in 6LoWPAN are expected to be deployed in extremely large numbers and they are expected to have limited compute, display and input capabilities, it makes network management critical in 6LoWPAN. The Simple Network Management Protocol (SNMP) is a widely used application protocol for network management and information control. In this paper, a network management architecture of 6LoWPAN based on SNMP is designed, including SNMP agents for constrained devices supporting IEEE 802.15.4 Radios and Contiki Embedded Operating System and SNMP manager in real IPv6 network.